2017
DOI: 10.1074/jbc.m117.796367
|View full text |Cite
|
Sign up to set email alerts
|

1α,25-Dihydroxyvitamin D3 promotes bone formation by promoting nuclear exclusion of the FoxO1 transcription factor in diabetic mice

Abstract: 1α,25-Dihydroxyvitamin D (1,25(OH)D) is the active form of vitamin D, which is responsible for reducing the risk for diabetes mellitus (DM), decreasing insulin resistance, and improving insulin secretion. Previous studies have shown that 1,25(OH)D inhibited the activity of FoxO1, which has been implicated in the regulation of glucose metabolism. However, its function and mechanism of action in DM-induced energy disorders and also in bone development remains unclear. Here, using and approaches including osteobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 61 publications
3
19
1
Order By: Relevance
“…1,25(OH) 2 D 3 was also reported to improve calcium metabolism in thalassemic mice, especially to enhance intestinal calcium absorption to supply more calcium for bone formation 5 . Basically, 1,25(OH) 2 D 3 directly affects bone cells by activating osteoblast activities and induces bone formation or mineralization 36 . However, paradoxical actions of 1,25(OH) 2 D 3 on bone are found in both in vivo and in vitro studies 37 .…”
Section: Discussionmentioning
confidence: 99%
“…1,25(OH) 2 D 3 was also reported to improve calcium metabolism in thalassemic mice, especially to enhance intestinal calcium absorption to supply more calcium for bone formation 5 . Basically, 1,25(OH) 2 D 3 directly affects bone cells by activating osteoblast activities and induces bone formation or mineralization 36 . However, paradoxical actions of 1,25(OH) 2 D 3 on bone are found in both in vivo and in vitro studies 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, many strategies such as pharmacological agents and implant surface modifications attempted to increase osseointegration of implants in T2DM, but few of them are available as a routine treatment method in clinical settings. [3][4][5] Therefore, it is urgent to develop new treatment strategies to improve the osseointegration of implants in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether PI3K/Akt signaling participates in the effect of 1,25D on the biological function of primary osteoblasts in HG environment, cells were pretreated in a 2-h incubation of PI3K inhibitor LY294002 (LY29, 50 mol/l, Sigma). Given that 1,25D could induce a time-dependent Akt and FoxO1 phosphorylation as previously reported ( 35 ), relevant analysis was detected after a 2-h treatment of 1,25D. It was observed that p-Akt/Akt level increased when 1,25D was added in primary osteoblasts cultured in HG (p-Akt is the active form of Akt via phosphorylation), which implied that PI3K/Akt signaling was activated by 1,25D.…”
Section: Resultsmentioning
confidence: 53%